(untitled) (Reflection and Critique Law Magazine, 2020)
This article, of the exploratory type, deals with insertion of the hermeneutic-juridical principle in dubio pro natura, addressing aspects derived from the bibliographic research on the evolution of Environmental Law as autonomous and multidisciplinary Legal Science as well as tracing aspects regarding the rising of third generation rights, the occurrence of the valorization of diffuse rights, which demonstrate the relevance of the application and the paradigmatic changes in the Brazilian legal order. In due course, outlined by the deductive method a brief connection to the importance of protecting the Amazonian biome against the historical context of explorations and how they have been discussed in the courts through concrete cases by facing hard cases. In this way, the greatest purpose is, without exhausting the theme, to expose the view that with the remodeling of jurisprudence entails positive effects for environmental protection, especially in the Amazon, in order to construct an interpretative process capable of providing harmonization of the relationship of being human relationship with nature and to idealize a cultural change of environmental consciousness according to the constitutional dictates, even with the current risks of setbacks.